Efeitos de incêndios no balanço hídrico dos mananciais de uma grande metrópole neotropical: simulações usando o SWAT na interface solo-água-vegetação - Evandro Luís Rodrigues (2018)
The constancy of water supply in springs depends on the environmental services derived from soil-plant-topography interactions. Throughout the planet, forest fires constitute important agents of landscape transformation, interfering at multiple scales of the water and biogeochemical cycles. These fires destroy the plant cover, breaking the foundations of this delicate system and compromising therefore water availability. The Serra do Rola Moça state park (PERSM, MG, Brazil), harbors a complex of springs that supplies water to the city of Belo Horizonte and surroundings, the third largest Brazilian metropolis (5.873.841 inhabitants). This park is subjected to fires that often burn large extensions of campos, cerrado and gallery forests that are home to these springs. The effects of the fires on the water supply of this metropolis are unknown and, surprisingly, few studies have explored changes in spring water balance resulting from forest fires at a global level. In view of this knowledge gap, we used the hydrological model Soil and Water Assessment Tool – SWAT- to simulate the effects of fire on the aquifer recharge of the watershed that provides water to the region of Belo Horizonte. The model was fed and calibrated with historical hydroclimatic series, applying the regional fire regime for correct validation. In the first chapter, our results suggest that increasing burned campo and cerrado areas result in larger deficit of groundwater stock and reduce the flow of the springs. In addition, the model predicts pulsed floods in the rainy season and drought in the dry season. Because of the high frequency of fires in the PESRM in the last decades, in the second chapter we reconstructed the plant cover of the 1970’s using remote sensing techniques, and compared with the current cover. Our results estimated a shrinkage of 42% of forest together with expansion of campo and cerrado physiognomies. Possibly the forest retraction resulted from logging and fires that were theoretically more intense before the creation of the park in 1994. Simulations with SWAT suggest a partial disruption of the mechanisms that govern infiltration and runoff of rainfall, estimating annual losses of 18% of infiltrated water volume in the soil. Cumulative losses of groundwater recharge reduce the base flow of springs and lead to substantial water deficits that compromise the supply of the nearby urban area. This, associated with increasingly frequent years of drought and mining threats, lead to the hydrological collapse of the region. The results of this dissertation highlight the importance of evaluating the pressure imposed by fire associated with deforestation on terrestrial ecosystems with aquatic interface. Therefor, the use of models enabled simulations to predict and anticipate damages to urban water supply derived from the loss of ecosystem services provided by the vegetation cover.